Both silver ions and silver nanoparticles facilitate the horizontal transfer of plasmid-mediated antibiotic resistance genes. (1st February 2020) - Lu, Ji; Wang, Yue; Jin, Min; Yuan, Zhiguo; Bond, Philip; Guo, Jianhua
Abstract: Antibiotic resistance in bacteria is a growing threat to global human health. Horizontal gene transfer (HGT) of antibiotic resistance genes (ARGs) is recognized as the primary contributor to antibiotic resistance dissemination. Silver nanoparticles (AgNPs) are widely used in personal care products as antimicrobial agents. While heavy metals are known to induce antibiotic resistance in bacteria, it is not known whether AgNPs in the environment can stimulate the HGT of ARGs. Here, we report that both AgNPs and ionic silver Ag +, at environmentally relevant and sub-lethal concentrations, facilitate the conjugative transfer of plasmid-borne ARGs across bacterial genera (from the donor Escherichia coli K-12 LE392 to the recipient Pseudomonas putida KT2440). The underlying mechanisms of the Ag + - or AgNPs-promoted HGT were unveiled by detecting oxidative stress and cell membrane permeability, combined with genome-wide RNA sequencing and proteomic analyses. It was found that both Ag + and AgNPs exposure induced various bacterial responses that included reactive oxygen species (ROS) generation, membrane damage and the SOS response. This study exposes the potential ecological risks of environmental levels of AgNPs and Ag + for promoting the spread of ARGs and highlights concerns regarding the management of nanoparticles and heavy metals. Graphical abstract: Image 1 Highlights: Both silver ion and silver nanoparticle stimulate ARGs conjugation. ROS overproduction is a critical factor to promote conjugation. The enhanced conjugation could be prevented by adding a ROS scavenger. Silver nanoparticle promotes conjugation due to nano-physicochemical properties.